Ocurrencia y caracterización de escherichia coli resistente a cefalosporina de tercera generación mediado por la familia génica blactx-m en el curso del río Isinche Latacunga. - Bungacho Michilena, Melanie Lizeth (2021)
Antibiotics use as growth promoters, prophylactics, and empiric therapies is common in small-scale animal production in Ecuador’s rural zones. These practices promote the evolution of multidrug resistant bacteria (MDR) in animals. Animal’s feces disseminate MDR to the surrounding environment and rivers, from the contamination reaches people through the food chain. However, the characteristics of this pollution in our region remain largely unknown. Therefore, the aim of this study was to evaluate MDR pollution in a rural river, using E. coli as the fecal contamination indicator and third-generation cephalosporin- (3GC) resistance as the MDR marker. The Isinche River was sampled at 4 sampling points. Total E. coli and 3GC-resistant E. coli counts were estimated using filtration on TBX and TBX supplemented with ceftriaxone 3μg/mL. Phylogroups, blaCTX-M (Groups 1,2,8 and 9) and mcr-1 genes were studied by PCR. Susceptibility for twenty-one antibiotics belonging to 10 families was evaluated using Kirby-Bauer. SP1, at the born of the river, was free of 3GC-resistant E. coli. SP2, SP3 and SP4, influenced by animal production, showed a high contamination by 3GC-resistant E. coli, up to 8x101 3GC-resistant E. coli/mL and one 3GC-resistant E. coli/50 susceptible E. coli. One hundred four 3GC-resistant E. coli were isolated for further analysis. The isolates belonged to phylogroups D(67%), B2(13%) and A(1%). Resistance genes blaCTX-M and mcr-1 were detected in 96% and 6%, respectively. blaCTX-M Groups 1 and 9 were the most prevalent (56% and 38%), and groups 2 and 8 were registered in 1% of the isolates. This population profile is concordant with identified in community-onset infections. Using as a model Isinche River, our study provides a warning about the high potential of the rural rivers for spreading MDR E. coli. Therefore, implementing regulations based on state-of-the-art methods is strongly recommended.